Peran Ma’had Al-Jami’ah Walisongo dalam Mewujudkan Pendidikan Berbasis Islam Rahmatan Lil ‘Alamin - Ahmad Ismail (LP2M of Institute for Research and Community Services - UIN Walisongo, 2021)
Ma'had is part of an institution that has noble hopes to produce a generation of people who specialize in religious education. Because it is the main source of religious knowledge and a place for moral development of students. In this case, Ma'had al-Jamiah Walisongo became one of the successors to raise the spirit of students (students) under the auspices of the Walisongo State Islamic University, Semarang. The role of Ma'had al-Jami'ah Walisongo is very relevant to the discourse on developing the quality of students who are integrative between intellectuals and morals. Through the Islamic-based ma'had curriculum, rahmatan Lil 'Alamin focuses more on classical book education and the development of students' talents and morals which are the strengths of UIN Walisongo Semarang Education to erode the problems of liberal and radical understanding and free morals that are controlled by the modernization of knowledge among teenagers. This paper tries to contribute thoughts towards the development of Islamic-based education rahmatan lil 'Alamin which leads to the intellectual, spiritual and moral integration of students to answer the challenges of modernizing the development of science that continues to develop at this time.Ma’had merupakan bagian lembaga yang memiliki harapan budi luhur untuk mencetak generasi bangsa yang mengkhususkan dirinya pada pendidikan keagamaan. Karena itu menjadi sumber utama pengetahuan agama dan tempat pembinaan moral anak didik. Dalam hal ini Ma’had al-Jamiah Walisongo menjadi salah satu penerus untuk membangkitkan semangat anak didik (mahasiswa) yang berada dalam naungan Universitas Islam negeri Walisongo Semarang. Peran Ma’had al-Jami’ah Walisongo sangat relevan dengan wacana pengembangan kualitas mahasiswa yang bersifat integrative antara intelektual dan moral. Melalui kurikulum ma’had yang berbasis Islam rahmatan Lil ‘Alamin lebih mengfokuskan pada Pendidikan kitab klasik dan pengembangan bakat dan akhlak mahasiswa yang menjadi kekuatan Pendidikan UIN Walisongo Semarang untuk mengikis problematika paham liberal dan radikal serta bebas moral yang dikuasai oleh arus modernisasi pengetahuan dikalangan remaja. Tulisan ini mencoba memberikan sumbangsih pemikiran kearah pengambangan Pendidikan berbasis Islam rahmatan lil ‘Alamin yang mengarah kepada integrasi intelektual, spiritual dan moral mahasiswa untuk menjawab tantangan modernisasi pengembangan ilmu pengetahuan yang terus berkembang saat ini.